THE EFFECTIVE, EFFICIENT USE OF SOCIAL MEDIA TO PROMOTE BUSINESS IN MARKETPLACE (CASE: UMKM OF KELURAHAN PONDOK PETIR, KECAMATAN BOJONGSARI, DEPOK CITY) - Taryo, Taswanda; Susanto, Agung Budi; Mardiyanto, Mardiyanto; Syarifudin, Syarifudin; Nafiah, Nafiah; Agustian, Rizki; Hilman, Amirul (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs, UMKM) have an important role in improving the family's economy in Pondok Petir Village, called “Cireng Village”, Bojongsari District, Depok City. In this Community Service (PKM) activity, a very relevant title of Utilization of Social Media to Promote a Business in Marketplace was raised. A lot of very suitable products are ready for Internet publication, such as, various kinds of chips, drinks, herbs, honey, groceries and cireng. Here, business actors are still doing it conventionally and have not made much use of technology, especially the internet. The products owned by MSME business actors are then not widely known by customers. PKM of Magister for Informatics Engineering UNPAM was finally carried out and hence Pondok Petir Village MSMEs can increase their product sales. Indeed, many MSMEs are finally expected to become reliable business actors not only locally, but also nationally and internationally.